2023
DOI: 10.3390/plants12203625
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Effect of Pruning on Growth, Quality, and Yield of Wuyi Rock Tea

Qi Zhang,
Ying Zhang,
Yuhua Wang
et al.

Abstract: Pruning is an important agronomic measure in tea plantation management. In this study, we analyzed the effect of pruning on gene expression in tea leaves from a transcriptomics perspective and verified the results of a transcriptomic analysis in terms of changes in physiological indicators of tea leaves. The results showed that pruning enhanced the gene expression of nine metabolic pathways in tea leaves, including fatty acid synthesis and carbohydrate metabolism, nitrogen metabolism, protein processing in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Zhang et al discovered that pruning tea plants enhance the accumulation and metabolism of sugar substances, accelerate the synthesis and transport of phytohormones and fatty acids, and thus improve the adaptive capacity of tea plants. It is beneficial for promoting tea plant growth and increasing tea yield [4]. In this study, the analyses of KEGG and GO revealed that DEGs significantly enriched in the pathways of plant-pathogen interaction, phytohormone signaling, and circadian rhythms in pruned tea plant spring buds.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Zhang et al discovered that pruning tea plants enhance the accumulation and metabolism of sugar substances, accelerate the synthesis and transport of phytohormones and fatty acids, and thus improve the adaptive capacity of tea plants. It is beneficial for promoting tea plant growth and increasing tea yield [4]. In this study, the analyses of KEGG and GO revealed that DEGs significantly enriched in the pathways of plant-pathogen interaction, phytohormone signaling, and circadian rhythms in pruned tea plant spring buds.…”
Section: Discussionmentioning
confidence: 67%
“…Pruning is a common and crucial practice in tea garden management [3]. It regulates branch growth and new growth of tea plants by inducing phytohormones [4]. Shaping Agronomy 2024, 14, 1105 2 of 16 of tea plants affects the yield and quality of fresh tea leaves [5], and pruning can change the branching habit of the natural growth of the tea plants to extend the crown to the peripheral space, promote nutrient growth, and eliminate apical dominance, increase bud sprouting, and lead to an increase in the rate of photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins rarely act alone but form complexes or interact with other proteins to perform most biological functions [56,57]. The protein-protein interaction (PPI) is a network in which the proteins interact in a living organism, helping to uncover key core genes [58].…”
Section: Protein-protein Interaction Network Analysismentioning
confidence: 99%
“…Plants can adopt different strategies to cope with the effects of stress. Zhang et al [ 24 ] reported that tea plants increased their own growth capacity to resist environmental stress. Waadt et al [ 25 ] reported that phytohormone synthesis rapidly increased when plants were under stress.…”
Section: Introductionmentioning
confidence: 99%